Analysis and Modeling of a Five- Level Inverter (International Journal of Engineering and Computer Science, 2017)
Multilevel inverters are mainly used in high power applications, where they have proved to be reliable and robust. They operate with low frequency and present high efficiency. Current demand on different reliable, efficient and robust inverters for different energy system has extended multilevel application to small power system as well. In this project, an inverting system will be developed using the cascaded H-bridge multilevel inverter technology, which is able to synthesize a desired ac voltage from several levels of dc Voltages. Multilevel inverter as compared to single level inverters have advantages like minimum harmonic distortion, reduced EMI/RFI generation and can operate on several voltage levels. A multi-stage inverter is being utilized for multipurpose applications, such as active power filters, and in many renewable energy power applications. The PWM signal thus generated is then used as triggering pulses for the multilevel inverters. This Project aims at the simulation study of single phase cascaded H- bridge multilevel inverter using DC voltages MATLAB software. It will be used to investigate and verify the quality of the ac output voltage, harmonic content of the output voltage and effects of different switching scheme.